Analysis of Student Satisfaction with Facilities and Infrastructure at the Dormitory of Universitas Negeri Medan: A Quantitative Descriptive Approach - Sihotang, Harry Marcel Wahyu; Manullang, Juliana Citra; Sagala, Prihatin Ningsih; Turnip, Leonardo; Sitorus, Tabhita Yolanda; Lubis, Nazwa Indri (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the level of student satisfaction with the facilities and infrastructure available at the Medan State University (Unimed) Dormitory. Adequate facilities have an important role in creating a comfortable learning environment and supporting academic productivity. This research uses a descriptive quantitative approach through a survey method, by distributing questionnaires to 23 respondents who are dormitory residents. The results of the analysis show that the level of student satisfaction with dormitory facilities varies. The security and comfort aspects of the study rooms received positive responses, while the availability of water, bathroom cleanliness, and the quality of the internet network are still factors that cause dissatisfaction. Although most respondents expressed satisfaction with the general cleanliness of the dormitories, improvements are still needed in terms of management services, facility maintenance, and the development of supporting infrastructure. The conclusion of this study shows that although some aspects of the facilities have met the standards, improvements are still needed in the management of facilities and infrastructure to increase student satisfaction. Improving the quality of facilities is expected to create a dormitory atmosphere that is safer, more comfortable, and conducive to the continuity of the student academic process.